Molecular Diagnosis, Prevalence and Importance of Zoonotic Vector-Borne Pathogens in Cuban Shelter Dogs—A Preliminary Study - Díaz-Sánchez, Adrian Alberto; Corona-González, Belkis; Meli, Marina L.; Roblejo-Arias, Lisset; Fonseca-Rodríguez, Osvaldo; Pérez Castillo, Anisleidy; Vega Cañizares, Ernesto; Lobo Rivero, Evelyn; Hofmann-Lehmann, Regina (Pathogens (Basel), 2020)
The present study aimed to determine the prevalence of zoonotic vector-borne pathogens, including Anaplasma platys, Anaplasma phagocytophilum, Borrelia burgdorferi sensu lato, Ehrlichia canis and Rickettsia spp. in shelter dogs from Cuba. Blood samples were collected from 100 shelter dogs and examined by molecular methods. Overall, 85 (85%; 95% CI: 77.88–92.12) dogs tested positive for at least one vector-borne pathogen using species-specific qPCR assays. Among the positive samples, E. canis was the most prevalent 62% (95% CI: 52.32–71.68), followed by A. platys 40% (95% CI: 30.23–49.77) and Rickettsia felis 27% (95% CI: 18.15–35.85), whereas 36% (95% CI: 26.43–45.57) showed co-infections. All samples were negative for A. phagocytophilum and B. burgdorferi s.l. The presence of 248 Rhipicephalus sanguineus ticks collected from the dogs was not statistically associated with the occurrence of infections. Thrombocytopenia was the most frequent haematological alteration found in PCR-positive dogs; it was statistically associated with the presence of E. canis, as well as co-infections (p < 0.05). The phylogenetic analyses of A. platys and E. canis based on 16S rRNA, groEL and gltA genes showed a low genetic diversity between Cuban strains. The present study demonstrates the high prevalence of vector-borne pathogens with zoonotic potential in shelter dogs from Cuba.